Examining the Feasibility of Acceptance and Commitment Therapy Self-Help for Problematic Pornography Viewing: Results From a Pilot Open Trial. (October 2017) - Levin, Michael E.; Heninger, Scott T.; Pierce, Benjamin G.; Twohig, Michael P.
This pilot study evaluated the feasibility of an acceptance and commitment therapy (ACT) self-help program for problematic pornography viewing (PV). A sample of 19 adults seeking help for problematic PV was recruited in an open trial. Participants reported adequate program acceptability, although only 45% of those completing postassessment read at least half of the self-help book. Significant improvements on problematic PV and cognitive fusion were found over the 8-week intervention period, with effects sustaining at 8-week follow-up. Participants who read more improved more on PV problems and psychological inflexibility. Overall, an ACT self-help approach appears feasible and potentially efficacious for PV.